Increasing cataract surgery to meet Vision 2020 targets; experience from two rural programmes in east Africa. Issue 10 (16th September 2005) - Lewallen, S; Roberts, H; Hall, A; Onyange, R; Temba, M; Banzi, J; Courtright, P
Abstract : Background: The numbers of cataract surgeries done in sub-Saharan Africa fall short of Vision 2020 targets. Over a few years, two programmes in rural east Africa both achieved significant increases in the number of cataract surgeries they provide, resulting in cataract surgical rates of 1583 for Kwale District in Kenya and 1165 for Kilimanjaro Region in Tanzania. Key components of success in these two programmes are described. Methods: Data were collected on standard indicators and key personnel interviewed to describe the results and compare the methods employed to increase cataract surgical rates by the Kwale District Eye Centre programme and the Kilimanjaro regional Vision 2020 programme. Results: Key components of success shared by the programmes included: (1) programmes in the community and at the hospital are closely linked so that they increase capacity together; (2) community programmes are "patient friendly, " providing service in one stop; (3) the examination team includes eye workers with enough skill to provide treatment and decide who is operable so that patients are not transported needlessly or sent through a lengthy referral chain; (4) sites for visits in the community are selected according to population distribution and they are visited according to a regular schedule. Conclusion: The development of "bridging strategies" that create a strong link between hospitals providing clinical service and communities needing these services is a key component to realising Vision 2020 goals in sub-Saharan Africa.